2006
DOI: 10.1016/s0929-6646(09)60183-2
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and Biochemical Factors Predicting SARS Fatality in Taiwan

Abstract: Initial neutrophil count, CRP and LDH levels are important predictors of mortality from SARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Our results are in agreement with previous narrative review 32 . Previously, liver damage has been reported as an important risk factor for severe outcome and death in SARS and MERS [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with previous narrative review 32 . Previously, liver damage has been reported as an important risk factor for severe outcome and death in SARS and MERS [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…For Hong Kong and Taiwan, it was reported that HCWs had a lower CFR than non‐HCWs (2.0% vs. 21.8% and 11.4% vs. 25.3%, respectively; Leung et al. 2004; Chang et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in LDH levels in the acute phase of SARS infection has been postulated to be possibly related to immune hyperactivity [30]. High peak LDH levels have been reported to be an independent predictor of adverse outcome [31][32][33][34]. Thus patients with SARS who are homozygous for CC genotype of the ICAM3 Asp143Gly SNP are associated with a 4-fold chance of higher LDH levels on admission and poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%